Polska Ludowa wobec ludności autochtonicznej na przykładzie ziemi babimojskiej = The people's Republic of Poland towards the indigenous population using the example of Babimost Lands - Nitschke, Bernadetta (1964- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
While raking over the western and northern terrains in 1945, the Polish country did not havea clearly defined policy towards the Polish indigenous population. Russian and Polish soldiers entering these areas, as well as Polish administrative authorities, had oftentimes treated themas Germans or half-Germans, and thus as the enemy.
Keywords: Babimojszczyzna; autochtoni; stosunki polsko-niemieckie; Polska - historia; po 1944 r.